Perbaikan Status Zat Besi oleh Suplementasi Teh Hijau pada Talasemia Tergantung-Transfusi: Tinjauan Sistematik dan Meta-Analisis: Tinjauan Sistematik - Susanto, Wiliam Prayogo; Karim, Cecy Rahma (Cermin Dunia Kedokteran, 2026)
Introduction: Iron overload significantly contributes to organ dysfunction in transfusion-dependent thalassemia (TDT) patients. Green tea extract (GTE), rich in polyphenols with iron-chelating properties, has shown promise in reducing iron levels in these patients, although its effectiveness remains unclear. This study aims to evaluate the impact of GTE on iron status in TDT patients. Methods: A systematic search of the PubMed, Embase, and Cochrane Library databases was conducted up to July 2024, identifying randomized clinical trials (RCTs) based on predefined criteria. Iron status was assessed through serum ferritin, total iron binding capacity (TIBC), serum iron, and transferrin saturation. Five RCTs involving 217 participants were included. Results: There has been a significant reduction in serum ferritin in the GTE group compared to controls (mean difference MD -0.55, 95% CI: -0.81, -0.29) and a similar reduction in serum iron (MD -63.73, 95% CI: -106.46, -21.00). Significantly higher TIBC and lower transferrin saturation were also observed in the GTE group. Conclusion: These findings suggest that GTE supplementation lowers serum ferritin and serum iron in TDT patients. Further research with larger cohorts is needed to better understand the effects on diverse populations.